Outcome Effects on Recidivism Among Drug Court Participants. (January 2019) - Gibbs, Benjamin R.; Lytle, Robert; Wakefield, William
Drug courts were established to reduce recidivism rates for substance-involved offenders who traditionally would have been sentenced to conventional probation supervision. Past research has reported success in this area, but much of the success is limited to those who graduate the program. Scholars have yet to examine the impact case outcomes and criminal sentencing have on post-participation reoffending. Yet, literature exists outside the area of drug courts, suggesting criminal sentencing, such as incarceration, may have a negative effect on offender recidivism. The current study addresses this gap in the drug court recidivism literature by examining the impact four outcomes of drug court participation (i.e., case dismissal, probation, jail, and prison) have on participant reoffending. We analyzed case outcome records of 824 drug court participants using propensity score analysis to isolate the effect criminal sentencing has on recidivism. Findings, potential policy implications, and directions for future research are discussed.